Treatment of a woman with emetophobia: a trauma focused approach - Ad de Jongh (Mental Illness)
A disproportionate fear of vomiting, or emetophobia, is a chronic and disabling condition which is characterized by a tendency to avoid a wide array of situations or activities that might increase the risk of vomiting. Unlike many other subtypes of specific phobia, emetophobia is fairly difficult to treat. In fact, there are only a few published cases in the literature. This paper presents a case of a 46-year old woman with emetophobia in which a trauma-focused treatment approach was applied; that is, an approach particularly aimed at processing disturbing memories of a series of events which were considered to be causal in the etiology of her condition. Four therapy sessions of Eye Movement Desensitization and Reprocessing (EMDR) produced a lasting decrease in symptomatology. A 3-year follow up showed no indication of relapse.